2008
DOI: 10.1590/s1806-37132008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de transtornos emocionais e comportamentais em adolescentes com asma

Abstract: Objective: To determine the prevalence of emotional and behavioral disorders in adolescents with asthma and to compare it with that of adolescents without asthma. Methods: A transversal study using the Strengths and Difficulties Questionnaire, administered to adolescents with or without asthma, ranging from 14 to 16 years of age and randomly selected from schools in the city of Belo Horizonte, Brazil. Results: The prevalence of emotional and behavioral disorders in adolescents with and without asthma was 20.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…Our study confirms and extends previous research of atopic disease in association with mental health problems by addressing hay fever along with eczema and asthma, and by adjusting for parental SEP in a large population-based study of children at different ages. 4 6 8 9 19–22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirms and extends previous research of atopic disease in association with mental health problems by addressing hay fever along with eczema and asthma, and by adjusting for parental SEP in a large population-based study of children at different ages. 4 6 8 9 19–22 …”
Section: Discussionmentioning
confidence: 99%
“…For asthma, an association with internalising problems (ie, anxiety and depressive symptoms) has been shown, 4 5 whereas evidence of a relation with externalising problems (ie, oppositional and hyperactive symptoms) is less clear. 5 6 In a meta-analysis of 26 observational studies, McQuaid found increases in internalising and externalising problems for children with asthma compared with children without asthma. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Os termos pesquisados foram "Questionário de Capacidades e Dificuldades" e "Strengths and Difficulties Questionnaire", tendo sido identificados 11 estudos, sendo 10 deles desenvolvidos no Brasil. Por meio de leitura de seus conteúdos, verificou-se que dos 10 trabalhos desenvolvidos no Brasil, cinco relacionavam problemas de saúde mental (identificados pelo SDQ) a outras variáveis, como, por exemplo, peso ao nascer (Gallo et al, 2011), tabagismo (Menezes et al, 2011), bullying (Moura, Cruz & Quevedo, 2011), asma (Alvim et al, 2008) e variáveis do contexto familiar (Ferrioli, Marturano & Puntel, 2007). Quatro trabalhos utilizaram o SDQ para fins específicos, a saber: na identificação de problemas de atenção e hiperatividade (Anselmi et al, 2010), na identificação de características comportamentais de crianças leitoras (Stivanin, Scheuer & Assumpção Júnior, 2008), na investigação de desordens psiquiátricas infantis (Cury & Golfeto, 2003) e na avaliação do comportamento social na escola (Saud & Tonelotto, 2005), além de um estudo que abordou aspectos conceituais relativos ao SDQ (Fleitlich et al, 2000).…”
Section: O Strengths and Difficulties Questionnaire No Brasilunclassified
“…Ansiedade, depressão, negação da doença e presença de conflitos familiares têm sido associados à menor adesão ao tratamento e maior morbimortalidade (Campanha, Freire & Fontes, 2008). A maioria dos estudos sobre a associação de transtornos emocionais e comportamentais e asma realizados em crianças e adolescentes mostra que eles têm maior prevalência de transtornos emocionais do que a população geral (Alvim, Ricas, Camargos, Lasmar, Andrade et al, 2008;Campanha, Freire & Fontes, 2008;Matos & Machado, 2008;Nogueira, Silva & Lopes, 2009;Salomão Júnior et. al.…”
Section: Palabras Clave: Asma Variables Psicosociales Enfoque Sistéunclassified
“…Para tanto, foram avaliados e quantificados os sintomas de ansiedade e depressão de 189 pacientes, sendo que a frequência de sintomas de ansiedade e depressão foi maior que entre aqueles com doença pulmonar obstrutiva crônica, o que pode dificultar o controle clínico. O estudo realizado por Alvim et al (2008) apontou para o fato de que adolescentes com asma têm mais sintomas de transtornos emocionais e comportamentais do que os adolescentes em geral. O presente trabalho reforça a necessidade de uma abordagem sistêmica (biopsicossocial), multi e interdisciplinar do adolescente com asma.…”
Section: Aspectos Psicológicos Como Fatores Agravantes Da Doençaunclassified